Padrões espaço-temporais da fisiologia da copa do cafeeiro - Santini, Paula Tristão (2015)
They have been mapped the eco-physiological and biochemical parameters of the coffee canopy metabolism. For this, the evaluations were conducted in coffee (Coffea arabica L.) cultivar Catuaí Vermelho, measuring 1.7 meters in height. It was established a vertical gradient (the apex of the plants to the base of the skirt) and a horizontal gradient (reproductive branches) to analyze different positions of the canopy. Thus, in the vertical direction were analyzed four times in a plant: top, top, middle and bottom, and horizontally, the reproductive branches were subdivided into three parts: basal, middle and apical, with the basal part one that gets smaller light intensity and the apical that receives higher. The gathering was held on the east and west side of the canopy, in four hours of the day, which are: 6, 9, 12 and 15 hours, totaling 24 sampling points in each zone. Gas exchange, water potential, biochemical analysis of cloroplastideos pigment content, carbohydrates and enzymes of antioxidant metabolism were made. The gas exchange characteristics of an individual coffee leaf differ considerably from other sheets, which requires caution when sizing estimates leaf photosynthesis globally canopy. It is necessary to understand the variable parameters within the coffee cup, since the change in metabolism varies according to the depth and height in a cup. The analysis of certain individual sheets does not serve to discriminate the global dynamics of a canopy.